ANALISIS PENGARUH KUALITAS LAYANAN INTI DAN PERIPHERAL TERHADAP KEPUASAN PELANGGAN DALAM MENINGKATKAN MINAT BELI ULANG (Studi pada Bengkel Ekauto Semarang) - Agustin, Fitrianiz; Rahardjo, Susilo Toto; Indriani, Farida (Master of Management Diponegoro University, 2016)
The purpose of this research is to test the influences of core service quality and peripheral service quality on customer satisfaction to increase repurchase intention. Using these variables, the usage of these variables are able to solve the arising problem within Bengkel Ekauto Semarang.The samples size of this research is 100 customers bengkel Ekauto Semarang. Using the Structural Equation Modeling (SEM). The results show that the core service quality and peripheral service quality on customer satisfaction to increase repurchase intention.The effect quality of core service quality on customer satisfaction are significant; The effect core service quality on repurchase intention are significant; The effect quality of peripheral service quality on customer satisfaction are significant; The effect peripheral service quality on repurchase intention are significant; and The effect customer satisfaction on repurchase intention are significant.